An evaluative study of the treatment program of approved schools / Yip Kam Tuck - Yip, Kam Tuck (1986)
A juvenile delinquent is not a criminal. Therefore, he should not be treated as one. Juvenile delinquency, as McGrath w. T. puts it, is a subdivision of crime and a special problem which society must deal with in its proper perspective. Juvenile delinquents need a special treatment program to put them on the right track again for . the juvenile ' s first brush with the law must also be his last. Is the treatment program of the approved schools of t his country special? Is it moving towards its objectives? These questions are the main pillar of the piece of evaluation study.